Episodic gaze deviation in multiple sclerosis – Versive seizures or oculogyric crises?. (December 2018) - Jamal Omidi, Shirin; Fernandez BacaVaca, Guadalupe; Lacuey, Nuria; Shaikh, Aasef G.; Morgan, Michael; Lhatoo, Samden D.
Highlights: Oculogyric crises and epilepsy have similar phenomenology with different mechanisms. OGC in patients with diffuse cerebral lesions can be difficult to diagnose from epilepsy. Video EEG monitoring is essential in differentiating OGC from epilepsy. Abstract: Ictal gaze deviation and oculogyric crisis (OGC) can show identical clinical manifestations. We report a case of repeated drug induced OGCs in a 38 year old patient with secondary progressive multiple sclerosis. He was referred to our center for treatment of "intractable" epilepsy manifesting as episodic eye and head deviations with apparent unresponsiveness. In the epilepsy monitoring unit, ten typical spells were captured without epileptiform electroencephalographic correlates, but we discovered chronic exposure to metoclopramide. A diagnosis of OGC was suspected and Metoclopramide was stopped. This robustly improved the frequency of his spells. In a setting of usage of antidopaminergic medications and/or pontomesencephalic lesions, a low threshold should be kept for the diagnosis of oculogyric crisis, thus avoiding seizure diagnoses and inappropriate treatment of the phenomenon. Video-EEG monitoring is essential for teasing apart epilepsy and OGC.